Ranking of Ustaz and Ustazah Popularity Levels to Understand Online Da'wah Expansion Strategies - Indra Silanegara; Maryono Maryono; Abdul Azis Abdillah (UMSU, 2022)
An acceptable reason is needed for choosing a religious figure to be researched, especially by users of the latest technology who have different perspectives. This paper aims to describe the steps to change the Google Trends function into a ranking tool for the level of popularity of Ustaz or Ustazah figures in cyberspace and then use it as material for further studies. The study began by searching for their names on Google Search using search queries: 'Ustaz' and 'Ustazah'. Directly, the first five names that appear are entered into the Google Trends app. Each name that has the lowest average graph among the five would be replaced by the next names, one by one. The name would be retained if the graph was higher and be ignored if it was lower. Thence, the ranking of Ustaz or Ustazah with the most sought-after information in cyberspace is generated. Tactical steps to find out how online users were interested in information (including dawah) from Ustaz or Ustazah were described in detail at the end of this paper.